EXPERIMENTAL STUDIES OF A MODEL FOR OPTIMIZING THE PORTFOLIO OF A PROJECT-ORIENTED ORGANIZATION BASED ON THE ENTROPY CONCEPT - Alla Bondar; Svitlana Onyshchenko (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of the research is the optimization of the composition of the project portfolio based on the entropy concept. The aim of the study is to experimentally test the model for optimizing the portfolio of a project-oriented organization and substantiate its applicability in practice in management processes to ensure their effectiveness. Research objectives: forming a model taking into account the accepted value of the organization; formation of initial data on the organization and alternative projects; portfolio optimization by model and interpretation of results. Research methods: system analysis, functional analysis, operations research. Results. A model has been developed for forming a portfolio structure from projects of two categories – operational and development; the optimization criterion is to minimize the discrepancy between the desired and actually provided value of the organization. The restrictions take into account the maximum allowable energy limit and the minimum allowable value limit. As a result of the study, the applicability and adequacy of the model for optimizing the portfolio structure of a project-oriented organization were substantiated.  The model makes it possible to obtain solutions on the optimal structure of a portfolio of projects in terms of its value under given resource constraints (in the form of a share of total energy and output energy) and energy entropy. The studies substantiated the possibility of adjusting the model in terms of the optimization criterion (maximizing value, minimizing energy entropy) and adding restrictions on the maximum permissible border of information entropy and energy efficiency. Conclusions. The model under consideration is characterized by wide practical application, taking into account its possible adjustment without changing the basic essence, taking into account the specifics of a particular field of activity or organization. The practical use of the main indicators of the entropy concept - information entropy, temperature, energy entropy, which characterize the state of organizations, allowing to identify hidden problems before they are reflected on the traditional indicators of organizational performance is demonstrated. Taking this into account, the structure of the project portfolio is being formed within the framework of the considered approach.